BodyKinetics: relationships between the representation of the human body and kinetic sculptures (Revista Apotheke, 2020)
This article presentes aspects related to the art that moves, or that only suggested movement, and the representation of human corporeality through Kinetic Art. By combining these two fields of investigation i am elaborating the concept of corpokineticism. Term that will give and example of mobile or installations that contain silhouettes of bodies moving with the wind interaction with the viewer or other any driving force used in kineticism. To achieve this goal i examined the production of artists who developed research and works involving mobility and representation of human body in Kinetic Art and other movements from the 19th century on, consequently finding references to the creative process elaborated in the research “Where are the Transcorpokinetic Tranny?” under development in the Associated Postgraduate Program in Visual Art UFPE/UFPB. Furthermore i intend with this text to contribute to the expansion of the concept of kineticism taking into account what Hans Belting says and the production of artists of brasilian Popular Culture, bringing works by the Masters Miró dos Bonecos, Saúba e Otávio, references When it comes to popular dolls and mobility toys. The literature review will be adopted as a methodology and authors such Argan (1992), Acher (2012), Krauss (1998) and Gombrich (2013) led me in Art History and Ostrower (2001) and Valente (2015) in Creativity. Finally, i presente some sketches and studies related to the creative process in process in the referred program and i conclude considering that the enjoyment of the works of classical artists and artists of Popular Culture contribute to sharpen my imagination. As well as the ideas and experiences present about the creative processes stimulated na incorporation both of the learning obtained in my creative trajectory and my own style/personality in the making of future works.
Keywords: travel; phenomenology; urban landscape